2015
DOI: 10.5735/086.052.0303
|View full text |Cite
|
Sign up to set email alerts
|

In situUnderwater Tagging of Aquatic Organisms: A Test Using the Cave-Dwelling Olm,Proteus anguinus

Abstract: In situ ecological studies on obligate cave-dwelling aquatic animals are scarce at best. This is particularly true for capture-mark-recapture (CMR) studies that form the basis of understanding population structure and dynamics. Here, we report on the in situ underwater application of the Visible Implant Elastomer (VIE) tagging system on the olm, Proteus anguinus, an obligate cave-dwelling aquatic amphibian. We tagged seven adult individuals and monitored the population during 31 dive transects during four year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The weak structure detected by the Bayesian assignment method could be caused by the effects of parent–offspring relatedness. On the other hand, cases of extreme philopatry over several years (Balázs, Lewarne, & Herczeg, ) and very restricted range sizes of some populations (Sket, ) indicate that other factors might confine dispersal in the karstic groundwater network.…”
Section: Discussionmentioning
confidence: 99%
“…The weak structure detected by the Bayesian assignment method could be caused by the effects of parent–offspring relatedness. On the other hand, cases of extreme philopatry over several years (Balázs, Lewarne, & Herczeg, ) and very restricted range sizes of some populations (Sket, ) indicate that other factors might confine dispersal in the karstic groundwater network.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed methodology of tagging can be found in Balázs et al (). Briefly, individuals were caught by hand and a black colour Visible Implant Elastomer (VIE, Northwest Marine Technology Inc., Shaw Island, WA, USA) was administered under their tail ‐ fin skin with a standard 29 gauge needle.…”
Section: Methodsmentioning
confidence: 99%
“…Thirteen individuals out of the 19 were recaptured later. During our pilot study (Balázs et al , ), we also tagged seven adults in 2010. Two individuals out of the seven were also recaptured during the 2016 tagging period and again afterwards; hence, these individuals were also included in the analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tagging sh in situ with acoustic transmitters at the same depth as capture and release has become more popular as studies have shown the negative effects of barotrauma on sh survival (Rummer and Bennett 2005; Rundershausen et al 2014). Externally tagging sh in situ has been reported for multiple studies (Atkins et al 2014, Balázs et al 2015, Sigurdsson et al 2006, and internally tagging sh in situ has become more common. For example, Starr et al (2000) captured deep-sea greenspotted rock sh (Sebastes chlorostictus) at depths between 100-200 m, brought them up to 20 m where they were internally tagged, then lowered them back down to depth and released them.…”
Section: Introductionmentioning
confidence: 99%